Global, regional, and national trends - von Grebmer, Klaus; Bernstein, Jill; Hossain, Naomi; Brown, Tracy; Prasai, Nilam; Yohannes, Yisehac; Patterson, Fraser; Sonntag, Andrea; Zimmerman, Sophia-Maria; Towey, Olive; Foley, Connell (International Food Policy Research Institute, 2017)
As the issue of famine looms large, it is easy to lose sight of the progress that has been made in the fight against hunger and undernutrition. The 2017 Global Hunger Index shows positive developments on many fronts, but there are still deep inequalities in hunger and undernutrition at the regional, national, and subnational levels. Too many people lack access to the quantity and quality of food they need. And too many people are not healthy enough to nutritionally benefit from food, for example, because infectious diseases prevent them from properly absorbing nutrients. The United Nations’ Sustainable Development Agenda includes the goal of ending hunger worldwide, while “leaving no one behind” (UN 2015). Examining hunger through the lens of inequality brings into sharper focus those populations, at all levels, who have so far been left behind. As we make progress in combating hunger, we should apply lessons learned and concentrate attention and resources on the areas where hunger and undernutrition are still unacceptably high in order to further decrease hunger in the future.